2020
DOI: 10.3390/v12050551
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the CD81 Binding Site and β-Sandwich Area in E2 of HCV in Cambodia

Abstract: The high genetic variability of hepatitis C virus (HCV) is the main obstacle to developing a vaccine. E2 has attracted attention for vaccine development because targeting this protein could potentially overcome issues related to the genetic diversity of HCV. In this study, we analyzed HCV genes in the general population of Cambodia and investigated the E2 locus as a candidate for vaccine development. HCV sero-epidemiological surveys were conducted between the period 2010 and 2014, with an HCV RNA–positive rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
1
1
1
Order By: Relevance
“…HCV genotype 1b (47.8%) and 6 (30.4%) were predominant in the current study. This finding is consistent with several previous studies in Cambodia, which reported HCV genotype 1b and 6 as the common genotypes observed in Cambodia [ 6 , 15 , 16 , 22 , 23 ]. The genotype 6 variant was also found as the most common in Vietnam and Laos [ 22 ], in blood donors in some regions of Thailand [ 16 ] and in intravenous drugs users in China [ 17 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…HCV genotype 1b (47.8%) and 6 (30.4%) were predominant in the current study. This finding is consistent with several previous studies in Cambodia, which reported HCV genotype 1b and 6 as the common genotypes observed in Cambodia [ 6 , 15 , 16 , 22 , 23 ]. The genotype 6 variant was also found as the most common in Vietnam and Laos [ 22 ], in blood donors in some regions of Thailand [ 16 ] and in intravenous drugs users in China [ 17 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also showed that the mutation rate between the first and second waves was 34.9-40.6 nucleotides per year, corresponding to 1.17-1.36 × 10 −3 base substitutions per site per year. This mutation rate is lower than that of hepatitis C virus [13]. A recent study reported that the mutation rate of SARS-CoV-2 in variable sites was 3.5 × 10 −3 changes per site per year, higher than the value we measured [14].…”
Section: Plos Onecontrasting
confidence: 83%
“…While HCV antibody prevalence was comparatively high in Papua New Guinea at 4.2%, only one small study among blood donors (n = 1206) was identified [ 10 ] and this estimate may not be representative of the general population. HCV antibody prevalence was also comparatively high at 3.9% in Cambodia where, similarly, only one small study (n = 868) was identified [ 11 ], However, hepatitis C viraemic prevalence in this setting was substantially lower at 1.3%. Mongolia was a notable exception, with this review confirming the endemic nature of HCV in this setting [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
“…Refs. [ 10 , 11 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Table A1unclassified